2022
DOI: 10.3389/fneur.2022.961563
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in Chinese patients with cervical dystonia

Abstract: ObjectiveCognitive impairment (CI) in patients with cervical dystonia (CD) has been reported in many studies but with inconsistent findings. We investigated the prevalence, characteristics, and clinical factors related to CI in Chinese patients with CD.MethodsSixty-eight patients with CD and 68 healthy controls (HCs) were included in the study. Demographic and clinical data were investigated. A logistic regression analysis was conducted to discriminate the clinical factors associated with CI in patients with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…In addition, some studies checked for possible influence of anxiety and depression on the association between altered cognitive performance and case status, but no appreciable confounding effect could be detected. 6,9,10,14,19 This would suggest against the hypothesis that cognitive impairment is secondary to motor features (dystonia or tremor) or depression. Available data therefore indicated that mild cognitive impairment may be a feature associated with IAOD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, some studies checked for possible influence of anxiety and depression on the association between altered cognitive performance and case status, but no appreciable confounding effect could be detected. 6,9,10,14,19 This would suggest against the hypothesis that cognitive impairment is secondary to motor features (dystonia or tremor) or depression. Available data therefore indicated that mild cognitive impairment may be a feature associated with IAOD.…”
Section: Discussionmentioning
confidence: 99%
“…Altered cognitive performance was independent of motor symptoms in 7 of 10 studies that assessed the relationship between cognitive impairment and severity of motor symptoms. In addition, some studies checked for possible influence of anxiety and depression on the association between altered cognitive performance and case status, but no appreciable confounding effect could be detected 6,9,10,14,19 . This would suggest against the hypothesis that cognitive impairment is secondary to motor features (dystonia or tremor) or depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in letter VFT, participants have to produce as many words as possible beginning with Chinese characters "Tian," "Yue," and "Hao" (Boll et al, 1974;Liu et al, 2022). Paper-version SDMT (Smith, 1973) is a simple substitution task, which gives the participants 90 s to pair specific numbers with given geometric figures with written responses.…”
Section: Assessment Of Neuropsychological Functioningmentioning
confidence: 99%